A Cost‐Effective Approach to Simulation‐Based Team Training in Obstetrics. Issue 6 (December 2014) - Chichester, Melanie; Hall, Nicole J.; Wyatt, Terri L.; Pomilla, Rosemarie
Abstract Many larger facilities regularly stage obstetric drills in modern simulation departments equipped with expensive simulators. Despite lacking these resources, we wanted to provide effective simulation training at our rural hospital. A team of clinicians and educators developed a cost‐effective and time‐efficient simulation drill for nurses, which included both a didactic review and a simulation day. The drill included obstetric providers and incorporated scenarios for shoulder dystocia, neonatal resuscitation and postpartum hemorrhage. This was a successful multidisciplinary learning experience that was high in creativity and teamwork, but low in cost. DOI: 10.1111/1751‐486X.12162